Effect of vesicular arbuscular mycorrhiza on rooting of black pepper (Piper nigrum L.) - SARMA, M ANANDARAJ, Y R (Journal of Spices and Aromatic Crops, 1994)
Incorporation of vesicular arbuscular mycorrhiza (VAM) fungus Glomus fasciculatum in the rooting medium of sand enhanced rooting of black pepper (Piper nigrum) cuttings. The rooting was reduced when the commercial rooting hormone (Ceradix B) was also added in addition to VAM. Rooting enhancement could be used as a cirterion to identify efficient strains of VAM for black pepper.